Comparison of laparoscopic-assisted vaginal hysterectomy, total abdominal hysterectomy and vaginal hysterectomy: A four years retrospective study in tertiary care centre - Padvi, Namrata Vasant; Ghumare, Jitendra Pundalik (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Hysterectomy is one of the commonest gynaecological operations performed in India. Traditional surgical treatments performed are abdominal hysterectomy and vaginal hysterectomy. Vaginal and laparoscopic procedures are considered “minimally invasive” surgical approaches because they do not require a large abdominal incision and, thus, typically are associated with shortened hospitalization and postoperative recovery times compared with open abdominal hysterectomy. With the aid of laparoscopic procedure, a potential abdominal hysterectomy can be converted to a vaginal one and a difficult vaginal hysterectomy can be converted into a fairly simple vaginal hysterectomy. Aim of the present study is to compare above methods of hysterectomy in terms of operating time, estimated blood loss, and postoperative hospital stay and complication, so as to provide best course of treatment to patient. Methods: A retrospective observational study was conducted in tertiary care centre. Four-year data was collected from January 2012 to December 2016. Cases of LAVH with benign gynaecological condition and up to 12 weeks size uterus, without any associated medical condition were selected in study randomly, and compare with cases of NDVH, TAH in terms of duration of operative procedure, blood loss during surgery, and postoperative hospital stay. Results: In present study we found that average duration of procedure in LAVH was 84.35 minute, which was maximum compare to other method. Estimated blood loss in LAVH was least as compare to NDVH and TAH it was maximum. The average hospital stays in LAVH and NDVH was less as compared to TAH. Conclusions: LAVH should be considered a better approach in view of the relatively less blood loss and intraoperative complication. Due to lack of large randomized controlled trials, the role of Laparoscopic hysterectomy is difficult to define.